Hermansky-Pudlak syndrome subtype 5 (HPS-5) novel mutation in a 65 year-old with oculocutaneous hypopigmentation and mild bleeding diathesis: The importance of recognizing a subtle phenotype. (2nd January 2018) - Botero, Juliana Perez; Chen, Dong; Majerus, Julie A.; Coon, Lea M.; He, Rong; Warad, Deepti M.; Pruthi, Rajiv K.; Nichols, William L.
Abstract: Hermansky-Pudlak syndrome (HPS) − characterized by the distinct clinical phenotypes of both oculocutaneous albinism and mild bleeding diathesis–is caused by mutations in genes that have crucial roles in the assembly of cellular organelles (skin melanosomes, platelet delta [dense] granules, lung lamellar bodies, and cytotoxic T-cell lymphocyte granules). Immunodeficiency, pulmonary fibrosis and granulomatous colitis are associated with some, but not all subtypes of HPS, with varying degrees of clinical severity. We describe a patient diagnosed with platelet dense granule storage pool deficiency (DG-SPD) at age 38 years after he presented with spontaneous intracranial hemorrhage. His mild oculocutaneous hypopigmentation was subtle. In the following 27 years, he did not develop severe bleeding nor pulmonary or gastrointestinal complications. A novel homozygous c.1960A>T; p.Lys654* mutation in the HPS-5 protein gene ( HPS5 ) was identified through next generation sequencing, (NGS) which is consistent with the patient's clinical and laboratory phenotypes. This case underscores the importance of recognizing the mild clinical phenotype of HPS-5 and utilization of both laboratory and molecular testing for diagnosis, prognostication, and surveillance for end organ damage in patients affected with HPS.